2008
DOI: 10.1016/j.jacc.2008.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cell Recovery Between Comparator Polymer-Based Drug-Eluting Stents

Abstract: The present study marks the first comparator analysis of endothelial coverage in leading polymeric DES, supporting disparities in arterial healing based on endothelial regrowth and recovery, favoring newer designs over the current generation of FDA-approved stents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
407
1
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 604 publications
(436 citation statements)
references
References 46 publications
20
407
1
8
Order By: Relevance
“…[8][9][10][11][12] The positive clinical results may reflect superior drug characteristics, polymer morphology, 13,14 and biocompatibility, [15][16][17] which may account for a better endothelialisation compared with older-generation DES. 18 When we started the present study no data from prospective randomised head-to-head comparisons between these two DES in a real-world scenario were available. Accordingly, the TWENTE study was designed to evaluate the clinical outcome of randomised use of Endeavor Resolute versus Xience V stents in a non-selected patient population.…”
mentioning
confidence: 99%
“…[8][9][10][11][12] The positive clinical results may reflect superior drug characteristics, polymer morphology, 13,14 and biocompatibility, [15][16][17] which may account for a better endothelialisation compared with older-generation DES. 18 When we started the present study no data from prospective randomised head-to-head comparisons between these two DES in a real-world scenario were available. Accordingly, the TWENTE study was designed to evaluate the clinical outcome of randomised use of Endeavor Resolute versus Xience V stents in a non-selected patient population.…”
mentioning
confidence: 99%
“…In a recent paper, the same group of investigators compared endothelial coverage after implantation of four different DES (SES, PES, everolimus-eluting stent (EES) and ZES) for 14 and 28 days along with a BMS control in the rabbit iliac artery. 31 While the endothelialisation ratio decreased in this study compared with overlap stenting, they now reported a significant disparity in endothelialisation at 14 days as compared with 28 days. EES and BMS demonstrated a greater endothelial coverage above struts, but remained poorest in SES, followed by PES and ZES.…”
Section: Preclinical Studies On Endothelialisationmentioning
confidence: 50%
“…Additionally, pre-clinical studies with stent implantation in animals with induced atherosclerosis are currently recommended 12,13 . When endothelialization data from Inspiron ® sirolimuseluting stents (Scitech ® , Goiânia, Brazil) are compared to the experimental data from Joner et al's study 14 as regards stent strut endothelialization, we verify that the Inspiron ® stent endothelialization rate (99%) is higher than that of other drug stents (Cypher ® : 64%, Taxus ® : 68%, Endeavor ® : 76% and Xience V ® : 80%) for the same observation period of four weeks post-implantation. This difference may result from the sirolimus elution only in the abluminal aspect in the Inspiron ® stent, whereas the antiproliferative drugs are released from both stent aspects in the other stents.…”
Section: Discussionmentioning
confidence: 99%